English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

simultaneous equation

2007-01-28 12:57:50 · 12 answers · asked by Novlette B 1 in Science & Mathematics Mathematics

12 answers

2x+3y=11
4x+2y=10
multiple the top equation by -2
-4x-6y=-22
4x+2y=10
-4y= -12
y=3
then plug 3 for y so 2x+9=11
2x=2
x=1 and y=3

2007-01-28 13:09:09 · answer #1 · answered by Anonymous · 0 0

are....you putting a homework question on here...?

I'm not gonna tell u the answer...but i'll walk u thru it...and u can trust me cause i'm asian and all asians are good at math xP

1. Isolate a variable (for example x)
2. So you'd have 2x = 11-3y (after subtracting)
3. Divide by 2....
4. Now you should have x to equal something...
5. Plug the value of x into the other equation and solve.
6. If you can't figure it out from there, you're either just retarded or lazy xD

lol good luck

-the asian

2007-01-28 13:03:21 · answer #2 · answered by holes44266 2 · 1 1

2x+3y=11
4x=2y=10
multiply the bottom equation by -1/2 to get
2x+3y=11
-2x-y=-5
add the equations to get
2y=6
solve for y
y=3
put this into one of the original equations
2x+3(3)=11
2x=11-9=2
solve for x
x=1
This can also be solved using "Cramer's Rule"

2007-01-28 13:14:11 · answer #3 · answered by beboe007 1 · 0 0

Multiply the first equation by 2 and the second equation by -3:
4x+6y=22
-12x-6y=-30
=========
-8x=-8
x=1

2(1)+3y=11
2+3y=11
3y=9
y=3

The solution set is (1,3)

Check:
2(1)+3(3)=11
2+9=11
11=11

4(1)+2(3)=10
4+6=10
10=10

I hope this helps!

2007-01-28 13:07:17 · answer #4 · answered by Anonymous · 1 1

There are different ways to solve this.
One easy way is to double the first equation and subtract the second one from it:
2x+3y=11
multiply by 2
4x+6y=22
subtract second equation
4x+6y=22
-4x-2y=-10
_________
4y = 12
y = 3
Now substitute y=3 anywhere
4x +6(3)=22
4x = 4
x =1
So: x=1 and y = 4

2007-01-28 13:05:19 · answer #5 · answered by ignoramus 7 · 2 1

Addition to Ignoramus
x = 1 and y = 3

2007-01-28 13:08:47 · answer #6 · answered by Sheen 4 · 0 1

First, multiply (2x+3y=11) by 2;
Second, subtract the two terms in order to delect x;
Third, slove for y;
Four, plug y in either one, solve for x.

I hope you can do the Math by yourselve, I think it's more benifial for long terms.

2007-01-28 13:08:33 · answer #7 · answered by That One! 3 · 1 0

4x+6y=22 , 4x+2y=10

22-6y=10-2y

22-10=6y-2y
12=4y
y=3

4x+2(3)=10
4x=4
x=1

2007-01-28 13:39:51 · answer #8 · answered by lost 2 · 0 0

dood. thats an equation for a line. just move it around a bit and graph the lines and walla! u have ur answer.

2007-01-28 13:00:37 · answer #9 · answered by randomdood 2 · 1 0

lol i may be wrong but i got
1.(0,3 2/3)
(5 1/2 , 0)

2. (0,5)
(2 1/2 , 0)

Im Dumb do iunno

2007-01-28 13:01:36 · answer #10 · answered by Anonymous · 0 1

fedest.com, questions and answers